G464(P) Building referral mechanisms for newborn care in humanitarian emergency settings: a systematic review. (25th October 2020) - Rutherford, S; Zaka, N; Leak, K; Cupp, M; Hafezi, H; Alexander, E; Lakhanpaul, M; Manikam, L
Abstract : Aim: During humanitarian emergencies, women and children are particularly vulnerable to health complications, and neonatal mortality rates rise. Additionally, health cluster partners face challenges in coordinating referrals from communities and camps to health facilities, and between different levels of health facilities. The purpose of this review was to identify the primary referral needs among neonates during humanitarian emergencies, current gaps and barriers, and effective mechanisms for overcoming these barriers. Methods: A systematic review was performed using 4 electronic databases (CINAHL, EMBASE, Medline, and Scopus) and multiple grey literature sources between June and August 2019. Title, abstract, and full text screening were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The target population was neonates born during humanitarian emergencies. Studies from high-income countries and prior to 1991 were excluded. The STROBE checklist was used to assess for risk of bias. Results: A total of 35 articles were included in the analysis; these were mainly qualitative, field-based studies. The primary needs identified were referrals from homes to health facilities before and during labour, and inter-facility referrals after labour to more specialised services. Some of the main barriers included a lack of roads and infrastructure for transport, a deficiency of specialised equipment for complications, staff shortages – especially among more specialised services, and a lack of knowledge among healthcare workers for identifying neonatal referral issues. Effective mechanisms for addressing these needs and gaps included establishing pre- or post-natal home visits by Community Health Workers or Traditional Birth Attendants; standardised, inter-facility referral checklists and procedures for healthcare staff; and staff training programmes for identification of neonatal complications. The severity and issues varied significantly between different countries and emergencies. Conclusion: This review benefited from a strong consensus among selected studies but was limited in the quality of data and types of data that were reported. Based on the above findings, the following recommendations were compiled: Recruit community healthcare workers to raise awareness and reduce pressure on health facilities. Establish contextualised programmes that address local needs and draw on local resources. Continue to train healthcare workers to provide timely, appropriate and quality care during humanitarian emergencies.